Graduates: reasons to study Nutrition as a profession - Universidad Nacional Mayor de San Marcos, 2006 - Quintana, Margot (2007)
Objective: To identify the reasons why graduates chose Nutrition as their professional career. Design: Quali-quantitative and exploratory research. Setting: Professional Academic School of Nutrition of San Marcos National Major University. Participants: Nutrition graduates. Interventions: After informed consents, two focus groups with 7 participants each, two in-depth interviews and a questionnaire to 34 former students were provided. Main outcome measures: Reasons why they chose, continued and finished their Nutrition studies. Results: In summary 73% of the participants were women, average age was 22,4 years, 30 students answered the questionnaire. They chose Nutrition because somebody personally told them about the career (30%), they learned of it at the pre-college academy (23%), possible transfer to another career (20%), and lower score required for admission (17%). They continued the career because the courses were interesting and they enjoyed the practical applications. They graduated from Nutrition because of many employment opportunities (73%), for health improvement contribution, and to work directly with the population. They felt good about their academic preparation but they wanted more practice and qualification in subjects like sport nutrition. Desired work included communitarian or clinical nutrition. Conclusions: The participants chose Nutrition due to external influences and convenience to transfer to another career, continued by motivating courses and graduated in this area due to opportunities on diverse labour fields.